Varieties of wedding (festivities and celebrations) in the Kazakh and Russian cultures - Dzhusupov, Mahanbet (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
The article deals with the problem of the cultural identity based on the analysis and description of the notions toi in the Kazakh language and Russian wedding. The content of the dictionary entries of these notions are investigated on the material of explanatory and bilingual dictionaries; differences of their content and structure are revealed. The Kazakh toi is totality of festive, banquets, celebrities which are celebrated owing to a change of social status of human. The toi owing to marriage is one of the varieties of the Kazakh toi, which is equivalent to the notion Russian wedding. Other varieties of the Kazakh toi (16 from 19) are not found in the Russian language and culture. However, the word toi is given as the equivalent of the word wedding in the bilingual dictionaries. The inherent content of the Kazakh toi in comparison with Russian wedding differs with its varieties, customs and rites. The Kazakh toi owing to marriage consists of two wedding ceremonies - in bridegroom’s house and in bride’s house. The cultural identity of the Kazakh toi and Russian wedding have common features, and at the same time they are substantially different, i.e. there is difference in similarity. These differences are demonstrated in monolingual and bilingual researches and are the causes of linguocultural interferences.